Redaction as Cross‐Regulatory Disclosure Avoidance - FLOROS, IOANNIS V.; JOHNSON, SHANE A.; ZHAO, WANJIA (Journal of Accounting Research, 2025)
ABSTRACT We introduce the idea of cross‐regulatory disclosure avoidance, whereby firms attempt to counteract expansions of disclosure under one regulation through actions that reduce disclosure under a different one. We study whether firms redact information from material contracts when they face new rules to disclose segment information. Using SFAS No. 131 as a plausibly exogenous shock to segment disclosure, we find that firms increasing the number of reported segments after the rule change exhibit a greater increase in redaction than firms maintaining the same number of segments. Consistent with proprietary cost motives, the increases are concentrated among firms with greater divergence in profitability across segments, higher abnormal segment profitability, and more negative abnormal stock returns in response to the finalization of the rule. Also, treated firms that redact after the rule change have abnormally profitable segments that they previously did not disclose. Firms that observables predict would increase redaction but did not experience declines in sales growth and profit margin. We find no evidence that agency cost motives drive the increases in redaction or, more generally, nondisclosure of segment performance before SFAS No. 131.